The Effect of Fuel Emulsion on Fuel Saving in Fire Tube Boilers of Tartous Company for Cement and Construction Materials (Journal of Solar Energy Research Updates, 2020)
In this work, the combustion of heavy oil and its emulsions with water, in the fire-tube boilers, was investigated in experiments on an industrial scale. The performance of the fire-tube boilers, used in Tartous company for cement and construction materials, was studied when they were employed to be operated with heavy fuel oil (HFO) and with the water phase of emulsified heavy oil containing 8 vol. % water and 92 vol. % heavy fuel oil (HFO). The emulsified water/heavy fuel oil (W/HFO) with 8 vol. % of water content showed no separation and contained the smallest and most homogeneous water-in-HFO (W/HFO) droplets after stability tests. Four boilers, each with 8 ton h-1 steam capacity, have been operated for 4 months with a regular heavy fuel oil HFO and W/HFO. It has been found that the micro-explosion, observed in W/HFO, improved the boiler efficiency and reduced the fuel consumption by 12.99%.